2021
DOI: 10.1111/jen.12858
|View full text |Cite
|
Sign up to set email alerts
|

The diversity and function of intestinal microorganisms in four geographic Cephalcia chuxiongica (a pine defoliator) populations

Abstract: There are abundant microbial communities in the digestive tract of insects. These microbes interact with insects actively to form an internal 'ecosystem', which plays essential roles in host physiology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
(100 reference statements)
1
5
0
Order By: Relevance
“…The present study and previous studies [21][22][23] on C. chuxiongica suggest that this species has evolved multiple physiological and behavioral strategies (such as facultative parthenogenesis, long larval diapause, and trade-offs on reproduction and survival) to adapt to its living environment.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The present study and previous studies [21][22][23] on C. chuxiongica suggest that this species has evolved multiple physiological and behavioral strategies (such as facultative parthenogenesis, long larval diapause, and trade-offs on reproduction and survival) to adapt to its living environment.…”
Section: Discussionsupporting
confidence: 65%
“…C. chuxiongica has a long (19 months) larval dormancy stage and adults do not feed [21], which may force adults to use limited resources optimally on reproduction and survival. In addition, C. chuxiongica females lay eggs on the surface of pine needles [23], which will facilitate larval feeding after hatching but also will likely to incur attack by natural enemies. C. chuxiongica females may thus have evolved egg protection behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the citrus fruit fly, Bactrocera minax , 16S rDNA sequencing revealed that Proteobacteria were dominant in gut and reproductive organs (Wang et al, 2014 ). Other studies have also found an abundance of Proteobacteria in various insect species, such as the sawfly Cephalcia chuxiongica (Yu et al, 2021 ), the desert locust Schistocerca gregaria (Dillon et al, 2010 ), the Lutzomyia sand fly (Sant'anna et al, 2012 ), and two ground beetles (Lundgren et al, 2007 ). Proteobacteria may play important roles in insects, such as help insects to fix nitrogen and preventing the establishment or proliferation of pathogenic bacteria (Dillon and Dillon, 2004 ; Dixon and Kahn, 2004 ; Behar et al, 2005 ).…”
Section: Discussionmentioning
confidence: 94%